A review on the recent history of wind power ramp forecasting. (December 2015) - Gallego-Castillo, Cristobal; Cuerva-Tejero, Alvaro; Lopez-Garcia, Oscar
Abstract: Forecasting large and fast variations of wind power (the so-called ramps) helps achieve the integration of large amounts of wind energy. This paper presents a survey on wind power ramp forecasting, reflecting the increasing interest on this topic observed since 2007. Three main aspects were identified from the literature: wind power ramp definition, ramp underlying meteorological causes and experiences in predicting ramps. In this framework, we additionally outline a number of recommendations and potential lines of research.